Validity of the evaluation of alcohol consumption established by the technical document of global evaluation of HIV-infected adults - Musayón-Oblitas, Yesenia (2023)
Objectives: To determine the validity of the evaluation of alcohol consumption established by the national strategy to prevent and control STI-HIV-AIDS (ESNITSS) of HIV-infected adults that started anti-retroviral treatment (ART). Methods: Diagnostic study of HIV patients in a single hospital in Lima from September 2017 to January 2018 using data from a phase one study “Effectiveness of nursing counseling in improving adherence to ART among patient with alcohol consumption”. Three hundred and fifty patients were randomly selected among 4000 participants. Two gold standards evaluated alcohol consumption: 1. Last month alcohol consumption and ii; alcohol consumption identified by the Alcohol Use Disorders Identification Test (AUDIT). Sensitivity, specificity, safety of the evaluation and probability rates. Results: sensitivity and specificity were moderate for last month alcohol consumption (s=0.64; e=0.57); specificity was low for evaluation of consumption risk (e=0.48). Positive validity rates demonstrated that the evaluation is not useful (<2). Conclusions: The evaluation of alcohol consumption followed by the ESNITSS has no diagnostic utility.